2020
DOI: 10.1021/acsabm.0c00312
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Magnetic Nanowires for Active Targeting and Enhanced Cell-Killing Efficacy

Abstract: 808nm Laser 1h incubation Dead cell Live cells Cell-death induction mechanism Specific targeting and destruction of colon cancer Magnetic field generator Nanowire (NW) Anti-CD44 antibody congregated NW (CD44-NW) CD44 antigens Colon cancer cell with CD44 antigens Dissipated heat Alternative Magnetic Field (AMF) Healthy cell doesn't have CD44 antigens Wash Magneto-mechanical Photothermal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 69 publications
(174 reference statements)
1
8
0
Order By: Relevance
“…Nanospinners can exert mechanical forces under a rotating magnetic field at 15 Hz and 40 mT to target the mitochondria of cancer cells [580]. Iron nanowires that are functionalized with anti-CD44 antibodies have been used in a combination therapy that included magnetomechanical and photothermal treatments on colon cancer cells [581]. Hedgehog-like microspheres that were composed of needle-like MNP with carbon and gold double shells seriously damaged cancer cells and strongly inhibited tumor growth through mechanical force [582].…”
Section: Magnetomechanical Methods For Cancer Therapymentioning
confidence: 99%
“…Nanospinners can exert mechanical forces under a rotating magnetic field at 15 Hz and 40 mT to target the mitochondria of cancer cells [580]. Iron nanowires that are functionalized with anti-CD44 antibodies have been used in a combination therapy that included magnetomechanical and photothermal treatments on colon cancer cells [581]. Hedgehog-like microspheres that were composed of needle-like MNP with carbon and gold double shells seriously damaged cancer cells and strongly inhibited tumor growth through mechanical force [582].…”
Section: Magnetomechanical Methods For Cancer Therapymentioning
confidence: 99%
“…The addition of active targeting compositions on these nanowires could produce a multifunctional tool to boost therapy efficacies through the combination of magnetic field treatments and specific target. Due to expression of the glycoprotein CD44 in about 90% of colon cancer cells, Fe NMWs were functionalised with anti‐CD44 antibodies for a combination therapy under magnetomechanical and photothermal treatments on colon cancer cells, leading to a 3‐fold increase of Fe NMWs internalisation in colon cancer cells compared to control cells, and the increased efficacy of killing from 35% of individual therapies alone to more than 71% of the combination therapy [129].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Studies have demonstrated that SIONs can effectively deliver cisplatin, curcumin, lauric acid, mitoxantrone, artemisinin, docetaxel, paclitaxel, dopamine, 10-hydroxycamptothecin, docetaxel, DOX, rifampicin, tetracycline hydrochloride, and other drugs ( Nagesh et al, 2016 ; Prakash et al, 2019 ; Vangijzegem et al, 2019 ). In addition, a few peptides, antibodies, or organic small molecules, such as amino-terminal fragment peptide ( Yang et al, 2009 ), anti-HER2/neu peptide ( Mu et al, 2015 ), anti-CD44 antibody ( Alsharif et al, 2020 ), prostate specific membrane antigen ( Bandini et al, 2017 ), β-cyclodextrin ( Sudha et al, 2016 ), and pluronic F127 polymer ( Khodaei et al, 2022 )were conjugated on the SION surfaces, consequently enhancing the targeting function of the SIONs delivery system, increasing the specificity and therapeutic effect.…”
Section: Classification Of Mnpsmentioning
confidence: 99%